Roles and Mechanisms of Interleukin-12 Family Members in Cardiovascular Diseases: Opportunities and Challenges - Ye, Jing; Wang, Yuan; Wang, Zhen; Liu, Ling; Yang, Zicong; Wang, Menglong; Xu, Yao; Ye, Di; Zhang, Jishou; Lin, Yingzhong; Ji, Qingwei; Wan, Jun (Frontiers in Pharmacology, 2020)
Cardiovascular diseases represent a complex group of clinical syndromes caused by a variety of interacting pathological factors. They include the most extensive disease population and rank first in all-cause mortality worldwide. Accumulating evidence demonstrates that cytokines play critical roles in the presence and development of cardiovascular diseases. Interleukin-12 family members, including IL-12, IL-23, IL-27 and IL-35, are a class of cytokines that regulate a variety of biological effects; they are closely related to the progression of various cardiovascular diseases, including atherosclerosis, hypertension, aortic dissection, cardiac hypertrophy, myocardial infarction, and acute cardiac injury. This paper mainly discusses the role of IL-12 family members in cardiovascular diseases, and the molecular and cellular mechanisms potentially involved in their action in order to identify possible intervention targets for the prevention and clinical treatment of cardiovascular diseases.